2021
DOI: 10.1016/j.jemermed.2020.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Emergency Department Use: Focus on Patients Requiring Urgent Revascularization

Abstract: Background The novel coronavirus (2019-nCOV) appeared in China and precipitously extended across the globe. As always, natural disasters or infectious disease outbreaks have the potential to cause emergency department (ED) volume changes. Objective We aimed to assess the influence of the Coronavirus Disease 2019 (COVID-19) pandemic on ED visits and the impact on the handling of patients requiring urgent revascularization. Methods We reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…A total of 52 studies reporting the impact of the COVID‐19 pandemic on stroke admissions were identified for qualitative synthesis. A total of 32,640 stroke admissions from 29 studies 6‐34 were included in the meta‐analysis (Figure 1) (Supplementary Table S1) based on a similar time frame of the study period and comparison period, of which ratios were derived, depending on each criterion data availability. Compared to the prepandemic period, the mean ratio of stroke admissions during the pandemic was 70.78% [95% CI: (65.02%, 76.54%)] (Figure 2) and the mean ratio of ICH cases was 83.10% [95% CI: (71.01%, 95.17%)] (Supplementary Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 52 studies reporting the impact of the COVID‐19 pandemic on stroke admissions were identified for qualitative synthesis. A total of 32,640 stroke admissions from 29 studies 6‐34 were included in the meta‐analysis (Figure 1) (Supplementary Table S1) based on a similar time frame of the study period and comparison period, of which ratios were derived, depending on each criterion data availability. Compared to the prepandemic period, the mean ratio of stroke admissions during the pandemic was 70.78% [95% CI: (65.02%, 76.54%)] (Figure 2) and the mean ratio of ICH cases was 83.10% [95% CI: (71.01%, 95.17%)] (Supplementary Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Montagnon et al, also found a similar increase in the proportion of elderly patients. (13) However, while we cannot have a particular reason for this, it can have resulted from the significant reduction in the proportion of patients younger than 16 years, from 33% and 22% in 2020.…”
Section: ❚ Discussionmentioning
confidence: 96%
“…Data on 115,716 adult emergency department visits to 108 emergency departments in the United States showed a significant reduction in the incidence of most of the serious cardiovascular events, with the exception of STEMI, in the year 2020 compared with that in 2019 ( 10 ). Similarly, no decrease in the number of patients presenting with STEMI was observed in France, and the authors of the study hypothesized that the pandemic probably dissuaded “non-critical” patients, but not those requiring reperfusion ( 11 ). In Greece, the number of patients presenting to the emergency department with acute coronary syndrome (ACS) in 2020 was significantly reduced compared to that in the previous year ( 12 ).…”
Section: Introductionmentioning
confidence: 94%